On geographers and ecological inference. - Johnston, Ron; Pattie, Charles (Annals of the Association of American Geographers, 2001)
A commentary on J. O'Loughlin's “Can King's Ecological Inference Method Answer a Social Scientific Puzzle: Who Voted for the Nazi Party in Weimar Germany?,” and D. Sui's “New Directions in Ecological Inference: An introduction,” both of which appeared in the Annals of the Association of American Geographers, vol. 90, 2000, pp. 592–601 and pp. 579–82 respectively. The writers discuss O'Loughlin's and Sui's comments on whether geographers, along with other social scientists, pay sufficient attention to studies of electoral geography to resolve the ecological inference problem. They argue that these comments demonstrate a lack of appreciation of a body of studies that sought resolve the ecological fallacy problem by estimating spatial variations in individual behavior. Details are provided of these studies.